2023
DOI: 10.1101/2023.05.30.23290568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-designing a theory-informed, multi-component intervention to increase vaccine uptake with Congolese migrants: a qualitative, community-based participatory research study

Abstract: Introduction Inequitable uptake of routine and COVID-19 vaccinations has been documented among intersectionally marginalised populations, including migrants, and attributed to issues of mistrust, access, and low vaccine confidence. Novel approaches which seek to share power, build trust and co-design tailored interventions with marginalised or underserved communities must be explored, to promote equitable engagement with vaccination and other health interventions. Methods A theory-informed, qualitative, commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This study originated from Congolese migrant community members identifying unmet needs and concerns around COVID-19 vaccination within their community, coupled with the academic partner's interest in exploring existing evidence gaps related to vaccination beliefs and behaviours among migrant populations (38)(39)(40). Within this CBPR study (reported elsewhere (41,42)), qualitative, semistructured in-depth interviews were conducted with Congolese migrants to explore their beliefs, perceptions and lived experiences of migration and healthcare in the UK, the COVID-19 pandemic, and routine and COVID-19 vaccination. The coalition co-designed and pilot-tested the topic guide and jointly decided on the data collection approaches and all aspects of the study design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study originated from Congolese migrant community members identifying unmet needs and concerns around COVID-19 vaccination within their community, coupled with the academic partner's interest in exploring existing evidence gaps related to vaccination beliefs and behaviours among migrant populations (38)(39)(40). Within this CBPR study (reported elsewhere (41,42)), qualitative, semistructured in-depth interviews were conducted with Congolese migrants to explore their beliefs, perceptions and lived experiences of migration and healthcare in the UK, the COVID-19 pandemic, and routine and COVID-19 vaccination. The coalition co-designed and pilot-tested the topic guide and jointly decided on the data collection approaches and all aspects of the study design.…”
Section: Methodsmentioning
confidence: 99%
“…Future research may now build on and test our findings and theoretical approach more purposively. We discuss other strengths and limitations of our work in our accompanying intervention co-design paper (76).…”
Section: Strengths and Limitationsmentioning
confidence: 99%